2013
DOI: 10.2133/dmpk.dmpk-12-rv-099
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Genetic Variation in OATP Transporters to Drug Disposition and Response

Abstract: There has been remarkable progress during the past decade in understanding of how genetic variations in drug metabolizing enzymes and transporters contribute to observed variation in drug responsiveness. Among drug transporters, the organic anion transporting polypeptide (OATP) class of transporters have proven to be remarkably important to the cellular uptake disposition of a variety of clinically important drugs, particularly in organs such as the intestine and liver; we now know that altered OATP activity m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(88 citation statements)
references
References 141 publications
(107 reference statements)
2
85
0
1
Order By: Relevance
“…This trend was also evident in the study with the largest sample size, in which OATP1B3 expression varied 8.8-fold in 64 subjects , in agreement with variability in OATP1B1 and OATP2B1 expression within the same study (up to 6.6-fold). In most of the studies, the extent of variability in protein expression exceeds the differences associated with the well-recognized genetic variations in the SLCO1B1 and SCLO1B3 genes encoding OATP1B1 and OATP1B3, respectively (Link et al, 2008;Niemi et al, 2011;Gong and Kim, 2013). However, direct analysis of any potential link between transporter genotype versus protein expression and, subsequently, functional activity was not possible because of the lack of data.…”
Section: Discussionmentioning
confidence: 99%
“…This trend was also evident in the study with the largest sample size, in which OATP1B3 expression varied 8.8-fold in 64 subjects , in agreement with variability in OATP1B1 and OATP2B1 expression within the same study (up to 6.6-fold). In most of the studies, the extent of variability in protein expression exceeds the differences associated with the well-recognized genetic variations in the SLCO1B1 and SCLO1B3 genes encoding OATP1B1 and OATP1B3, respectively (Link et al, 2008;Niemi et al, 2011;Gong and Kim, 2013). However, direct analysis of any potential link between transporter genotype versus protein expression and, subsequently, functional activity was not possible because of the lack of data.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to statins, examples of potential victim OATP substrates are repaglinide (antidiabetic), fexofenadine (antihistaminic), olmesartan and telmisartan (antihypertensives), and torsemide (diuretic) based on the literature (10,29). Furthermore, the number of such examples can be expected to increase as new OATP1B substrate drugs are developed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the effects of two major genetic polymorphisms in SLCO1B1, c.388A>G (p.130N>D) and c.521T>C (p.174V>A), on the pharmacokinetics and subsequent pharmacodynamics/toxicity have been extensively been studied. 41,42) Nishizato et al have found that c.521T>C mutation is tightly linked to c.388A>G mutation in Japanese with a high frequency and these mutations form a haplotype named SLCO1B1*15. 43) They conducted a clinical study in which the plasma concentration of pravastatin in subjects with *15 allele was significantly higher than that in subjects with *1b (c.388A>G) allele, which is the first demonstration of a relationship between genetic polymorphisms of SLCO1B1 and the pharmacokinetics of substrate drugs.…”
Section: Genetic Polymorphisms Of Oatp1b1 and Oatp1b3 And Their Clinimentioning
confidence: 99%